Superoxide dismutase 2 knockdown leads to defects in locomotor activity, sensitivity to paraquat, and increased cuticle pigmentation in Tribolium castaneum - Tabunoki, Hiroko; Gorman, Maureen J.; Dittmer, Neal Thomas; Kanost, Michael R. (My University, 2017)
Insects can rapidly adapt to environmental changes through physiological responses. The red flour beetle Tribolium castaneum is widely used as a model insect species. However, the stress-response system of this species remains unclear. Superoxide dismutase 2 (SOD2) is a crucial antioxidative enzyme that is found in mitochondria. T. castaneum SOD2 (TcSOD2) is composed of 215 amino acids, and has an iron/manganese superoxide dismutase domain. qRT-PCR experiments revealed that TcSOD2 was present through all developmental stages. To evaluate TcSOD2 function in T. castaneum, we performed RNAi and also assessed the phenotype and antioxidative tolerance of the knockdown of TcSOD2 by exposing larvae to paraquat. The administration of paraquat resulted in significantly higher 24-h mortality in TcSOD2 knockdown larval groups than in the control groups. The TcSOD2 knockdown adults moved significantly more slowly, had lower ATP content, and exhibited a different body color from the control groups. We found that TcSOD2 dsRNA treatment in larvae resulted in increased expression of tyrosinase and laccase2 mRNA after 10 days. This is the first report showing that TcSOD2 has an antioxidative function and demonstrates that T. castaneum may use an alternative antioxidative system when the SOD2-based system fails.
Citation: Tabunoki, H., Gorman, M. J., Dittmer, N. T., & Kanost, M. R. (2016). Superoxide dismutase 2 knockdown leads to defects in locomotor activity, sensitivity to paraquat, and increased cuticle pigmentation in Tribolium castaneum. Scientific Reports, 6, 8. doi:10.1038/srep29583
Keywords: Bombyx-Mori; Uric-Acid; Life-Span; Cocoon Shell; Silkworm; Drosophila